2015
DOI: 10.32677/ijch.2015.v02.i04.017
|View full text |Cite
|
Sign up to set email alerts
|

Awareness among mothers regarding oral rehydration salt solution in management of diarrhea: A cross-sectional study

Abstract: Background: Diarrhea remains one of the leading global causes of death among children under the age of 5 years; diarrhea and the resultant mortality from it is both preventable and treatable. Proper knowledge regarding the use of oral rehydration salt solution (ORS) helps in preventing morbidity and mortality from diarrhea. Objective: To assess the awareness, knowledge and practice of mothers of under-five children regarding the use of ORS and other alternative solution during diarrheal illness. Methods: A cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…4 Awareness of zinc supplementation in diarrhoea was poor as only 53(16%) mothers had used it in the current study, which was similar to 51(20.4%) reported from India. 17 In a hospital-based study in Rawalpindi, among mothers who were aware of the use of ORS, only 41.8% were also aware of the use of zinc. 4 In the present study zinc use in diarrhoea was significantly associated with maternal education (p-0.001) and SES (p=0.001).…”
Section: P R O V I S I O N a L L Y A C C E P T E D F O R P U B L I C ...mentioning
confidence: 99%
“…4 Awareness of zinc supplementation in diarrhoea was poor as only 53(16%) mothers had used it in the current study, which was similar to 51(20.4%) reported from India. 17 In a hospital-based study in Rawalpindi, among mothers who were aware of the use of ORS, only 41.8% were also aware of the use of zinc. 4 In the present study zinc use in diarrhoea was significantly associated with maternal education (p-0.001) and SES (p=0.001).…”
Section: P R O V I S I O N a L L Y A C C E P T E D F O R P U B L I C ...mentioning
confidence: 99%
“…This is similar with the results of a study done in Karnataka. 12 This also showed a significant association with good knowledge about ORS. In a study at Rawalpindi, Pakistan 13 showed that about 68% mothers always used ORS during diarrhoea, which is similar to this study.…”
Section: Discussionmentioning
confidence: 83%
“…Table (2) show that mother self-efficacy scale for preventing diarrhea concerning studied main domains since grand mean of score is evaluated moderate level.…”
Section: Self-efficacy Scale For Preventing Diarrhea Concerning Studied Main Domainsmentioning
confidence: 99%
“…A higher prevalence of diarrheal diseases in young children is associated with young age, low socioeconomic status (SES), poor maternal literacy, the involvement of under-five siblings in the household, low birth weight, insufficient breastfeeding, malnutrition, poor sanitation and poor maternal hygiene practices [2] .…”
Section: Introductionmentioning
confidence: 99%